Natural orifice specimen extraction with laparoscopic radical gastrectomy for distal gastric cancer: A case report - Sun, Peng (World J Clin Cases, 2019)
BACKGROUND: This article introduces the surgical method and early experience in performing totally laparoscopic radical gastrectomy with transrectal specimen extraction for gastric cancer, and we evaluate the short-term effects and feasibility of this new procedure for gastric cancer in a 64-year-old male patient. This approach may provide new possibilities for gastric natural orifice specimen extraction (NOSE) surgery. In addition, we believe that this new procedure may further relieve pain, speed up recovery, and cause minimal physiological and psychological impact. CASE SUMMARY: We performed NOSE gastrectomy in a male patient. Tumor resection, digestive tract reconstruction, and lymph node dissection were performed totally laparoscopically; the specimen was extracted from the natural orifice of the rectum-anus. This procedure reduced damage to the abdominal wall and decreased postoperative pain. We successfully performed radical gastrectomy without conversion and complications. Total operative time and blood loss were 176 min and 50 mL, respectively. The patient resumed normal activities of daily living on day 1 without pain, and passed flatus within 48 h. Postoperative hospital stay was 10 d. The number of resected lymph nodes was 0/43. During the follow-up, no stricture or anastomotic leakage was detected. Three months postoperatively, colonoscopy showed full recovery of the rectum without stricture or scar contracture. Computed tomography and laboratory test results showed no signs of tumor recurrence. There was no visible scar on the abdominal wall. CONCLUSION: It is safe and reliable to perform totally laparoscopic radical gastrectomy with transrectal specimen extraction for distal gastric cancer patients.